2022
DOI: 10.1111/jdi.13745
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal regulation of glucagon secretion and gluconeogenesis

Abstract: Hypoglycemia almost never develops in healthy individuals, because multiple hypoglycemia sensing systems, located in the periphery and in the central nervous system, trigger a coordinated counterregulatory hormonal response to restore normoglycemia. This involves not only the secretion of glucagon, but also of epinephrine, norepinephrine, cortisol and growth hormone. Increased hepatic glucose production is also stimulated by direct autonomous nervous connections to the liver that stimulate glycogenolysis and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Secretion of glucagon, which forms the first line of defence against hypoglycaemia, is controlled by multiple pancreatic-alpha-cell autonomous and non-autonomous mechanisms [ 2 ]. The role of central hypoglycaemia sensing in triggering glucagon secretion is well documented [ 3 ]. Neurons present in the brainstem, in particular in the dorsovagal complex, the parabrachial nucleus and the basolateral medulla, have been implicated in hypoglycaemia-induced glucagon secretion [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secretion of glucagon, which forms the first line of defence against hypoglycaemia, is controlled by multiple pancreatic-alpha-cell autonomous and non-autonomous mechanisms [ 2 ]. The role of central hypoglycaemia sensing in triggering glucagon secretion is well documented [ 3 ]. Neurons present in the brainstem, in particular in the dorsovagal complex, the parabrachial nucleus and the basolateral medulla, have been implicated in hypoglycaemia-induced glucagon secretion [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…since this administration route resulted in significant higher levels of this SGA in plasma and hypothalamus in comparison to those of the oral treatment [ 32 ]. As such, we focused the present study in the connection between the hypothalamus and the liver since it has been reported that this axis modulates lipid metabolism in response to T 3 [ 19 ] and glucose homeostasis in response to leptin [ 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…116 In addition to these well-described counter-regulatory hormonal responses, the central nervous system (CNS) also plays a critical role in the response to hypoglycemia (Figure 1). Animal models have been instrumental in elucidating the different brain regions and neuronal circuits that contribute to an integrated response to falls in plasma glucose levels (several excellent reviews [117][118][119][120] ). Glucose-sensing neurons have been identified in the hindbrain, midbrain, as well as several regions within the hypothalamus, including the arcuate nucleus, the perifornical region of the lateral hypothalamus, as well as the ventromedial hypothalamus (VMH).…”
Section: Physiologic Defenses Against Hypoglycemiamentioning
confidence: 99%